Nε-(carboxymethyl) lysine represses hair follicle formation by inhibiting Sonic hedgehog expression in a NF-κB-independent manner - Kosuke Tanaka; Kana Mizuno; Chika Natsume; Misaki Takanishi; Yuki Shimada; Ryo Saito; Norihisa Fujita; Takashi Fujita (International Journal of Dermatology and Clinical Research - Peertechz Publications, 2019)
Nε-(carboxymethyl) lysine (CML), an advanced glycation end product (AGE), is an aging factor produced by glycation of protein. Higher levels of AGE in skin tissue are related to skin elasticity, but how CML that has accumulated in the skin affects hair follicle formation is unclear. This study constructed a simple model that mimics accumulated glycation from feeding by intradermally injecting Nε-(carboxymethyl) lysine (CML), and examined the effects on the morphogenesis of hair follicles (HF). The results showed weakening of the hair shaft and HF formation by CML. The in vitro inhibitory effect of CML on wound healing of dermal papilla cells (DPC) suggested that the mechanism influences the proliferation and migration of DPC, which are essential for HF morphogenesis. In addition, CML in DPC inhibited the expression of sonic hedgehog (Shh), a factor of tissue morphogenesis, in a NF-kB-independent manner. The findings suggest that the delay in HF formation was due to CML inhibiting proliferation and migration in DPC by inhibiting Shh expression.